2016
DOI: 10.7205/milmed-d-15-00482
|View full text |Cite
|
Sign up to set email alerts
|

Eating Behaviors: Prevalence, Psychiatric Comorbidity, and Associations With Body Mass Index Among Male and Female Iraq and Afghanistan Veterans

Abstract: Disordered eating may be a significant issue among Iraq and Afghanistan veterans, and veterans with eating problems are more likely to have comorbid mental health conditions that further increase their health risks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…Data for the study were derived from the WVCS survey, described in detail elsewhere. 35,36 Eligible participants were military veterans of the OEF/OIF/OND era who enrolled for care in VHA settings between September 12, 2001 and September 30, 2012 (n = 625,082). A subsample of veterans participated in three surveys were administered yearly and recruited primarily via mailings sent to 8465 potential participants from eight states; female veterans were oversampled as a means to equalize numbers of male and female participants.…”
Section: Overview and Participantsmentioning
confidence: 99%
“…Data for the study were derived from the WVCS survey, described in detail elsewhere. 35,36 Eligible participants were military veterans of the OEF/OIF/OND era who enrolled for care in VHA settings between September 12, 2001 and September 30, 2012 (n = 625,082). A subsample of veterans participated in three surveys were administered yearly and recruited primarily via mailings sent to 8465 potential participants from eight states; female veterans were oversampled as a means to equalize numbers of male and female participants.…”
Section: Overview and Participantsmentioning
confidence: 99%
“…Increased healthcare use for individuals with EDs is particularly relevant to veterans. Aspects of military life and culture, including strict weight and physical fitness requirements, combat exposure, and military sexual trauma, may contribute to increased risk for the development of EDs among military and veteran populations (Bartlett & Mitchell, ; Slane et al, ). However, these populations are understudied in the field of EDs, which may lead to disparities in care.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, prior research among the general population has suggested that the eating disorder diagnostic categories might not accurately capture the clustering of eating pathology, as various studies have identified a number of latent classes or profiles that do not map onto the DSM classifications of eating disorders (e.g., Bulik, Sullivan, & Kendler, ; Crow et al., ; Keel et al., ; Wade, Crosby, & Martin, ). In addition, a large proportion of research on comorbidity in this area has examined individual or select eating disorders and PTSD (e.g., Grilo et al., ; Hoerster et al., ; Reyes‐Rodriguez et al., ; Rosenbaum et al., ) or general disordered eating and PTSD (e.g., Carmassi et al., ; Holzer, Uppala, Wonderlich, Crosby, & Simonich, ; Isomaa, Backholm, & Birgegard, ; Slane et al., ), leaving a lack of clarity regarding which eating disorder is most associated with PTSD. This supports the importance of identifying the broader pathological eating features most common in PTSD and highlights the benefit of examining maladaptive eating indicators/symptomatology associated with DSM‐5 eating disorders as opposed to the confines of eating disorder diagnoses specifically.…”
mentioning
confidence: 99%